In vitro fertilization following laparoscopic ovarian diathermy in patients with polycystic ovarian syndrome - Nicola Colacurci; Fulvio Zullo; Pasquale DeFranciscis; Antonio Mollo; Giuseppe DePlacido (Acta Obstetricia et Gynecologica Scandinavica, 1997)
Background. To evaluate the in vitro fertilization outcome in patients with polycystic ovarian syndrome previously treated by laparoscopic ovarian diathermy. Methods. We designed a prospective study to compare in vitro fertilization stimulation parameters and pregnancy rate for two groups of women with polycystic ovarian syndrome. In the first group, we included 23 patients previously treated by laparoscopic ovarian electrodia‐thermy (group A), in the second group we included 36 women who did not undergo surgical treatment (group B). All patients underwent the same ovarian hyperstimulation protocol and a standard in vitro fertilization and embryo transfer technique. In a limited number of women (five in group A and eight in group B) we measured the levels of sex steroids in follicular fluid. Statistical analysis was performed by means of chi‐square test or Fisher's exact test to compare frequencies and by means of the Student's t‐test or ANOVA test to compare means. Significance was set at p<0.05. Results. In group A we found a significantly higher ongoing pregnancy rate (28.6% in group A vs 7.3% in group B), a significantly lower estradiol peak level (1722.73 ± 522.24 in group A vs 2314.48 ± 692.60 in group B), a trend for lower abortion rates and an improvement in the number of patients administered human chorionic gonadotropin than in group B. The levels of estradiol, testosterone and androstenedione in follicular fluid were significantly lower from small to intermediate and to large follicles in group A, while in group B only estradiol and androstenedione were different. Lower levels of androstenedione and testosterone were found in each follicular pool of group A, compared to the respective pool in group B. Conclusion. We report a significantly better ongoing pregnancy rate after in vitro fertilization and embryo transfer procedures in women pretreated by means of laparoscopic ovarian electrocautery. These results may be related to lower androgen levels in the follicular fluid.